PENGARUH TINGKAT PEMAHAMAN AKUNTANSI, FUNGSI BADAN PENGAWAS DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN LEMBAGA PERKREDITAN DESA DI KECAMATAN GIANYA - Ni Kadek Pebriantari; Rai Dwi Andayani W (Hita Akuntansi dan Keuangan, 2021)
This study was intended to test the impact of accounting comprehension levels, the function of the supervisory body and the use of information technology on the quality of the LPD financial report in Gianyar district. The study uses independent variables, that is, accounting comprehension levels, the function of the supervisor's bodies, and the use of information technology. while the dependent variable is the quality of the financial report. The sample of this study were 102 respondents. Purposive sampling was used as a sampling method in this research. The data analysis technique includes descriptive analysis, multiple linear regression analysis, validity test, reliability test, classical assumption test, determination coefficient test (R2), F test and T test. Result of the Research shows that variable accounting levels do not affect the quality of financial statements. Meanwhile the function of the body of the supervisor and the use of information technology affects the quality of the financial report.